Development of Graphene Oxide/Polyethylene to enhance mechanical properties through melt mixing technique - Mohammad Amirul, Mohd Yusof; Nor Hafiz, Nor Rahman; Izirwan, Izhab; Mohd Shaiful Zaidi, Mat Desa; Ngahzaifa, Ab Ghani (Institute of Physics, 2023)
Graphene Oxide (GO) was added to Low-Density Polyethylene (LDPE) to test the mechanical properties of the compound. Compared to other types of polyethylene, LDPE provides a good balance of mechanical properties and processability, which leads to its being chosen as the research's matrix material. This experiment aims to prepare LDPE/GO through melt mixing technique and analyse mechanical properties of tensile strength/tensile elongation of LDPE/GO composite based on GO concentration (0, 0.5, 1.0 and 1.5 wt%). The compounding of LDPE/GO was blended using a five-stage twin-screw extruder under specific conditions before going through the moulding process at melting temperature. The composites were cut according to ASTM D638 specimen dimension. The tensile properties of LDPE composites were filled separately with different weight fractions of GO at a 50 mm/min rate. It was found that the values of Young's modulus of the composites increased, but the values of the tensile elongation at break decreased with increasing the GO weight fraction. The relatively big interfacial area and excellent interfacial adhesion between the matrix and the GO may be responsible for the composites' reinforcement. This study provided a basis for further development of GO-reinforced LDPE composites with desirable mechanical performance and good damage behaviour.